Analysis Of Mapping Multicopter Drones In The Entrance Area Of Prospective New Airports In Congot, Temon, Kulonprogo, Yogyakarta - Indreswari Suroso (Politeknik Negeri Batam, 2018)
This research use multicopter drone. This mapping was carried out at the entrance area of the prospective new airport precisely at the Congot beach area, Temon district, Kulonprogo district with a multicopter drone. This drone is capable of recording an altitude of 100 meters above ground level and can photograph an area of 1.5 km. This study used a drone type multicopter The vehicle specifications are as follows: Frame: F450; Flight Controller: DJI Naza M-Lite; Propeller: 1045 Prop; motorbike: brushless sunnsky 980 kVa; ESC: Skywalker 40 Ampere 3s; Battery: Ace 3s Gens 5000mAH; Remote: Turnigy 9XR with Frsky Tanseiver; and camera: Xiaomi Yi 4k International edition. The height of a multicopter drone reaches 30 meters, can take an area of up to 1 km and a flight time of 15 minutes. The advantage of this multicopter is that it uses a DJ I Phantom camera classified as stable for the light weight drone class. So for terrain with high wind speed, this multicopter drone is still able to maintain its position in the air. The Kulonprogo Regional Government and the Congot Radar Unit really appreciate this mapping because it is very helpful in mapping the entrance of new prospective airports in Kulonprogo.